Penerapan Akad Pembiayaan Syariah Dan Regulasinya Di Indonesia - Luqmanul Hakiem Ajuna (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2019)
AbstractThe article explained in detail about Islamic finance and the regulations in Indonesia. This is based on demand for sharia economic modernization in Indonesia which is expected to have an impact on the ease of transactions for all its countries. The literature study is based on the theory on the Qur’an and hadith to perfect  the regulations made by state institutions that are closely related to sharia finance in Indonesia. The Financial Services Authority (OJK) which had the function organizing a comprehensive system of regulation ans supervision the activities of financial services sector in Indonesia had a gread responsibility for the success and failure of Sharia financing company in Indonesia. Besides, OJK, it also includes the National Sharia Council (DSN) of the Indonesia Ulama Council (MUI) which stated halal and illegitimated financing transactions. The collaboration between two attributes of country that had a major contributions to sharia financial transactions in Indonesia has given birth to the products of sharia financing resulting from the development of contracts that strongly prohibit usury, garar, and maysir practioners. AbstrakArtikel ini menjelaskan secara detail dan rinci pembiayaan syariah dan regulasinya di Indonesia. Hal ini didasarkan pada tuntutan moderninasi ekonomi syariah di Indonesia yang diharapkan berdampak pada  kemudahan transaksi untuk seluruh warga negaranya. Kajian kepustakaan dilakukan berdasarkan pada teori yang disandarkan pada  Alquran dan hadis untuk menyempurnakan regulasi yang dibuat oleh lembaga-lembaga yang erat hubungannya dengan pembiayaan syariah di Indonesia. Otoritas Jasa Keuangan (OJK) yang berfungsi  menyelenggarakan sistem pengaturan dan pengawasan secara menyeluruh terhadap kegiatan sektor jasa keuangan di Indonesia memiliki tanggung jawab besar atas berhasil dan gagalnya perusahaan pembiayaan syariah di Indonesia. Selain OJK, Dewan Syariah Nasional (DSN) Majelis Ulama Indonesia (MUI) yang memfatwakan halal dan haramnya transaksi pembiayaan tersbut. Kolaborasi kedua atribut negara yang memiliki andil besar terhadap transaksi keuangan syariah di Indonesia ini telah melahirkan produk-pruduk pembiayaan syariah hasil dari pengembangan akad-akadnya yang melarang praktik riba, garar, dan maysir.